Effects of Omega-3 Fatty Acids Supplement on Antioxidant Enzymes Activity in Type 2 Diabetic Patients - Fatemeh TOORANG; Abolghassem DJAZAYERY; Mahmoud DJALALI (Tehran University of Medical Sciences, 2016)
Background: Diabetes is a major cause of death. Oxidative stress mainly caused by hyperglycemia is the primary reason of related complications. Omega-3 fatty acids are prescribed in diabetes but the effect on antioxidant defense is controversial. This study investigated effects of omega-3 supplementation on antioxidant enzymes activity in type 2 diabetic patients. Methods: A randomized, placebo controlled, double blind clinical trial was performed on 90 type2 diabetic patients. The treatment group took, daily, three capsules of omega-3 for two mo, which totally provided 2714mg omega-3 (EPA=1548 mg, DHA=828 mg and 338 mg of other omega=3 fatty acids). Placebo contained 2100 mg sunflower oil (12% SFA, 65% linoleic acid, 23% MUFA), which is the main oil used in the study population. Food intakes, anthropometric and demographic characteristics, and therapeutic regimen data were recorded before and after the intervention. Fasting blood samples were taken before and after the intervention to measure super oxide dismutase, glutathione peroxidase, glutathione reductase, catalase and total antioxidant capacity in erythrocytes. Results: A total of 81 subjects completed the study. Two study groups were similar as regards duration of diabetes, age and the enzymes at baseline. Energy and macro- and micronutrients intakes, weight and hypoglycemic agent consumption were similar in the two groups at baseline and did not change. Supplementation had no effect on antioxidant enzyme status. Glycated hemoglobin showed a significant reduction by supplementation. Conclusion: Daily supplementation of 2714 mg mega-3 for two mo results in a significant reduction in HbA1c level in type2 diabetic patients with no effects on antioxidant enzymes activity.